KOMITMEN AFEKTIF DALAM ORGANISASI, PERCEIVED ORGANIZATIONAL SUPPORT, DAN KEPUASAN KERJA - Han, Sia Tjun; Nugroho, Agustinus; Kartika, Endo W.; Kaihatu, Thomas S. (Jurnal Manajemen dan Kewirausahaan, 2013)
The research was quantitative explanative, which objectives included explaining relations between two or more variables. The data was gathered using questionnaire. In this research, Structural Equation Modelling (SEM) was used to answer the research questions. It was found out that perceived organizational support influenced both job satisfaction and affective commitment positively and significantly. However, it was also discovered that job satisfaction had a positive influence to affective commitment but it wass not significant.